Neboša Lazić: Vreme i prostor u Zlatnom runu Borislava Pekića, Univerzitetska biiblioteka u Beogradu, 2016 - Radosavljević, Anica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Abstract is not available in English.